Global Visions of Violence : Agency and Persecution in World Christianity - Kirkpatrick, David C.; Bruner, Jason (Book collections on Project MUSE., 2023)
"In Global Visions of Violence, the editors and contributors argue that violence creates a lens, bridge, and method for interdisciplinary collaboration that examines Christianity worldwide in the twentieth and twenty-first centuries. By analyzing the myriad ways violence, persecution, and suffering impact Christians and the imagination of Christian identity globally, this interdisciplinary volume integrates the perspectives of ethicists, historians, anthropologists, and ethnographers to generate new conversations. Taken together, the chapters in this book challenge scholarship on Christian growth that has not accounted for violence while analyzing persecution narratives that can wield data toward partisan ends. This allows Global Visions of Violence to push urgent conversations forward, giving voice to projects that illuminate wide and often hidden landscapes that have been shaped by global visions of violence, and seeking solutions that end violence and turn toward the pursuit of justice, peace, and human rights among suffering Christians"--